2021
DOI: 10.1111/ecc.13511
|View full text |Cite
|
Sign up to set email alerts
|

Multistakeholder knowledge levels and perspectives of human papillomavirus and its vaccination: An exploratory qualitative study

Abstract: Objective: This qualitative study was an integral part in the development of a multidisciplinary team-led school-based human papillomavirus vaccination healthpromotion programme (MDL-SHPVP) aiming to increase HPV vaccine uptake in Hong Kong. Study findings will inform the design of the MDL-SHPVP by drawing on interview data regarding the expectations and needs of key stakeholders and potential programme users.Methods: Eight mother-daughter dyads, four secondary school teachers, two school principals, three soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The exclusion of males is attributed to limited resources. Thus, nurses in under-resourced areas may be expected to exclude males from vaccine efforts despite the nurses’ willingness to implement gender inclusive promotion (Chau et al, 2021; Clavé Llavall et al, 2021). Female-only campaigns make it difficult for nurses to use a simplified message that centers around gender neutral cancer prevention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion of males is attributed to limited resources. Thus, nurses in under-resourced areas may be expected to exclude males from vaccine efforts despite the nurses’ willingness to implement gender inclusive promotion (Chau et al, 2021; Clavé Llavall et al, 2021). Female-only campaigns make it difficult for nurses to use a simplified message that centers around gender neutral cancer prevention.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly true for high-income countries like Australia and the United States (Burns et al, 2021; Rosen et al, 2019). In countries where vaccine resources are more limited, females remain the prioritized target population, but school nurses are ready and willing to support male vaccination (Chau et al, 2021; Clavé Llavall et al, 2021). There is widespread acceptance of inclusive HPV vaccination for adolescents among school nurses.…”
Section: Implications For Practicementioning
confidence: 99%
“…As part of a larger randomized controlled trial to evaluate the effectiveness of the MDL-SHPVP in raising HPV vaccination rates among female adolescents in Hong Kong, tailored educational resources were developed following the identification of relevant participant learning needs [7]. Resources primarily aimed to clear up misconceptions and provide essential information about HPV infection and HPV vaccination to potential vaccine recipients and facilitators.…”
Section: Discussionmentioning
confidence: 99%
“…Health education is a potentially effective solution to encourage vaccine acceptance and combat hesitancy. In a previous study, it was found that misconceptions and low knowledge levels of HPV are common among various stakeholders in Hong Kong [7]. By highlighting the relevance of the vaccine, addressing concerns regarding side effects and more, education can empower people in the decision-making process and instil confidence regarding the value of HPV vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Several HPV studies conducted in high as well as LMIC settings highlighted adolescents confused HPV with other sexually transmitted infections, such as herpes, human immunodeficiency virus, or gonorrhea, further contributing to misunderstandings about their personal risk of acquiring HPV and the purpose of HPV vaccines [28,40,43,[48][49][50][51].…”
Section: Plos Global Public Healthmentioning
confidence: 99%